EFFECTIVENESS OF THE APPLICATION OF NON-TRADITIONAL TRAINING AND RECOVERY MEANS IN BASKETBALL PLAYERS - Василенко, Вадим (SWorldJournal, 2025)
The article discusses the issues of a non-traditional system of training and recovery of basketball players